Newcastle disease as an emerging disease in peacocks of Tharparker, Pakistan - Mustafa, Irfan; Ahmed, Haroon; Lodhi, Myda Abrar; Siddiqi Sher Khan, Abdul Rauf; Haider, Waseem; Bostan, Nazish; Asif, Saira; Khan, Mobushir Riaz; Qayyum, Mazhar; Ali, Shahzad; Ali, Muhammad Ishtiaq; Afzal, Muhammad Sohail (The Journal of Infection in Developing Countries, 2015)
This item has no abstract. Follow the links below to access the full text.